First experimental feasibility study of VIPIC: a custom‐made detector for X‐ray speckle measurements. (12th February 2016) - Rumaiz, Abdul K.; Siddons, D. Peter; Deptuch, Grzegorz; Maj, Piotr; Kuczewski, Anthony J.; Carini, Gabriella A.; Narayanan, Suresh; Dufresne, Eric M.; Sandy, Alec; Bradford, Robert; Fluerasu, Andrei; Sutton, Mark
Abstract : Preliminary X‐ray correlation spectroscopy results from the novel three‐dimensional vertically integrated photon imaging chip (VIPIC) detector are presented. Abstract : The Vertically Integrated Photon Imaging Chip (VIPIC) was custom‐designed for X‐ray photon correlation spectroscopy, an application in which occupancy per pixel is low but high time resolution is needed. VIPIC operates in a sparsified streaming mode in which each detected photon is immediately read out as a time‐ and position‐stamped event. This event stream can be fed directly to an autocorrelation engine or accumulated to form a conventional image. The detector only delivers non‐zero data (sparsified readout), greatly reducing the communications overhead typical of conventional frame‐oriented detectors such as charge‐coupled devices or conventional hybrid pixel detectors. This feature allows continuous acquisition of data with timescales from microseconds to hours. In this work VIPIC has been used to measure X‐ray photon correlation spectroscopy data on polystyrene latex nano‐colliodal suspensions in glycerol and on colloidal suspensions of silica spheres in water. Relaxation times of the nano‐colloids have been measured for different temperatures. These results demonstrate that VIPIC can operate continuously in the microsecond time frame, while at the same time probing longer timescales.